2007
DOI: 10.1021/la701080u
|View full text |Cite
|
Sign up to set email alerts
|

Micro-BLMs on Highly Ordered Porous Silicon Substrates:  Rupture Process and Lateral Mobility

Abstract: In a recent paper, we hypothesized that the continuous increase in membrane conductance observed for nano-BLMs is the result of an independent rupturing of single membranes or membrane patches covering the pores of the porous material. To prove this hypothesis, we prepared micro-BLMs on porous silicon substrates with a pore size of 7 mum. The upper surface of the silicon substrate was coated with a gold layer, followed by the chemisorption of 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol (DPPTE) and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 25 publications
8
69
0
Order By: Relevance
“…These findings indicate that, apart from the obvious enhanced friction suffered by the molecules moving inside the pore rims of the patterned ZnO-2 film in comparison with the unpatterned sample (i.e., topographic effect), the presence of SiO 2 areas confined by the ZnO is relevant to trigger the protein mobility at the biointerface (i.e., chemical effect). Similar results, pointing to a friction-reduced lateral diffusion on pore rims compared with that of the area within the pore, have been reported for lipid membranes on ordered porous silicon substrates [42]. In our case, the protein diffusion rate on the hybrid ZnO-SiO 2 surface is likely be affected not only by the topography by also by the surface chemistry and charge.…”
Section: Protein Interaction With the Ultrathin Zno-based Filmssupporting
confidence: 90%
“…These findings indicate that, apart from the obvious enhanced friction suffered by the molecules moving inside the pore rims of the patterned ZnO-2 film in comparison with the unpatterned sample (i.e., topographic effect), the presence of SiO 2 areas confined by the ZnO is relevant to trigger the protein mobility at the biointerface (i.e., chemical effect). Similar results, pointing to a friction-reduced lateral diffusion on pore rims compared with that of the area within the pore, have been reported for lipid membranes on ordered porous silicon substrates [42]. In our case, the protein diffusion rate on the hybrid ZnO-SiO 2 surface is likely be affected not only by the topography by also by the surface chemistry and charge.…”
Section: Protein Interaction With the Ultrathin Zno-based Filmssupporting
confidence: 90%
“…In our case, the situation is even more complicated as the lipids on the CPEO3-monolayer experience larger friction due to a strong coupling compared to those in the freestanding region, which is expected to slow down the lateral lipid diffusion. [18] From the low immobile fraction of (11 AE 6) % it can be concluded that the CPEO3 monolayer is incomplete and contains non-immobilized lipids after formation of the pore-spanning membrane. If the CPEO3-monolayer completely prevented the bottom lipid monolayer to diffuse, an immobile fraction of about 50 % would be expected.…”
Section: Size and Lateral Mobility Of L O -Phase Domainsmentioning
confidence: 99%
“…The mechanical decoupling between neighboring holes via the chemically immobilized lower leaflet of the bilayer on the rim of a hole causes the individual rupturing of the suspended bilayer, providing a longer lifetime for the devices than the classical black lipid membrane, which loses its entire function in a single rupture event. 54 As the need for the development of more sophisticated ionchannel-based biosensing and high-throughput drug screening systems increases, a number of efforts have been aimed at achieving a GO seal between two aqueous compartments separated by lipid bilayers and improving their lifetimes to several days. The high membrane resistance required for a single ion channel measurement was attained by the formation of a lipid bilayer on a gold-coated porous alumina substrate with a surface was functionalized with 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol.…”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 99%